A new species of Psychrophrynella (Amphibia, Anura, Craugastoridae) from the humid montane forests of Cusco, eastern slopes of the Peruvian Andes - Catenazzi, Alessandro (2016)
We describe a new species of Psychrophrynella from the humid montane forest of theDepartment Cusco in Peru. Specimens were collected at 2,670_3,165 m elevation inthe Área de Conservación Privada Ukumari Llakta, Japumayo valley, near Comunidad Campesina de Japu, in the province of Paucartambo. The new species is readily distinguished from all other species of Psychrophrynella but P. bagrecito and P. usurpator by possessing a tubercle on the inner edge of the tarsus, and from these two species by its yellow ventral coloration on abdomen and limbs. Furthermore, the new species is like P. bagrecito and P. usurpator in having an advertisement call composed of multiple notes, whereas other species of Psychrophrynella whose calls are known have a pulsed call (P. teqta) or a short, tonal call composed of a single note. The new species has a snoutvent length of 16.1_24.1mmin males and 23.3_27.7mmin females. Like other recently described species in the genus, this new Psychrophrynella inhabits high-elevation forests in the tropical Andes and likely has a restricted geographic distribution.